Development in Design Stage Based on Risk to Reduce Variation Order in Building Construction Project at PT. XYZ - Bani Adlan Tedja; Ayomi Dita Rarasati (Journal of International Conference Proceedings, 2021)
The consultant planning is the key to create document design for project construction. In the world of construction, Variation order are frequent occurrence, many factors cause variation order is uncontrollable, the most common caused by consultant planning. The main task of consultant planning is to provide design architectural in drawing documentation and technical report document that enable contractor to make all of these idea into physical reality in the project. Design error, inadequate design, failure of design or lack of coordination area common cause of variation order by the consultant planning. For this reason, it needs a strategy in the design stage process in order to minimize the occurrence of variation orders. This study aims to identify the stage of design process, identify the risk that occur at the design stage that cause variation orders and the strategy to reduce variation orders caused by the consultant planning.